Neuroprotective Effects of the Pannexin-1 Channel Inhibitor: Probenecid on Spinal Cord Injury in Rats - Qi, Qi; Wang, Xiao-Xuan; Li, Jing-Lu; Chen, Yu-Qing; Chang, Jian-Rong; Xi, Jin; Lü, He-Zuo; Zhang, Yu-Xin (Frontiers in Molecular Neuroscience, 2022)
Proinflammatory immune cell subsets constitute the majority in the local microenvironment after Spinal Cord Injury (SCI), leading to secondary pathological injury. Previous studies have demonstrated that inflammasomes act as an important part to the inflammatory process after SCI. Probenecid, an inhibitor of the Pannexin-1 channel, can inhibit the activation of inflammasomes. This paper focuses on the effects of Probenecid on the local immune microenvironment, histopathology, and behavior of SCI. Our data show that Probenecid inhibited the expression and activation of NLRP1, ASC and caspase-1, IL-1β, and caspase-3 proteins associated with inflammasome, thereby suppressing M1 macrophages and increasing the differentiation of M2 macrophages. And consequently, the drug can reduce the area of fibrosis in spinal cord injury, promote the formation of white matter myelin. Altogether, the current studies indicate that Probenecid can alleviate inflammation by blocking Pannexin-1 channels to inhibit the expression of caspase-1 and IL-1β, which in turn restores the balance of immune cell subsets and exerts the neuroprotective effects in rats with spinal cord injury.